2020
DOI: 10.1002/smi.2978
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity to war stressors: An experience sampling study in people with and without different psychiatric diagnoses

Abstract: There is a lack of knowledge regarding real‐time emotional reactivity to high‐intensity stressors, particularly in people with mental illness, a potentially vulnerable population. The current study aimed to examine negative emotional reactions to recurring high‐intensity stressors within a continuous war situation, in people with different psychiatric diagnosis types. Experience sampling method was used to examine emotional reactions among 143 civilians exposed to rockets during the 2014 Israel–Gaza war, of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…In a study on of the 1991–1995 Balkan war, Croatian civilians with a psychiatric diagnosis suffered from higher levels of psychopathological distress than matched German individuals with a psychiatric diagnosis who were not exposed to war (Jovanovic et al., 2010). In an experience sampling methodology study of the same cohort as in the current study, during the 2014 Israel–Gaza war, participants with a psychiatric diagnosis had higher levels of three out of four PTSD symptom clusters, including negative cognitions (Gelkopf et al., 2017), but similar emotional and threat reactivity to rocket warning sirens compared to participants without a psychiatric diagnosis (Gelkopf et al., 2017; Lapid Pickman et al., 2021). Regarding service use and help seeking, one large study observed no change and even a reduction in psychiatric outpatient visits and hospitalizations during the 2000–2002 Intifada in Jerusalem (Levav, 2006).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a study on of the 1991–1995 Balkan war, Croatian civilians with a psychiatric diagnosis suffered from higher levels of psychopathological distress than matched German individuals with a psychiatric diagnosis who were not exposed to war (Jovanovic et al., 2010). In an experience sampling methodology study of the same cohort as in the current study, during the 2014 Israel–Gaza war, participants with a psychiatric diagnosis had higher levels of three out of four PTSD symptom clusters, including negative cognitions (Gelkopf et al., 2017), but similar emotional and threat reactivity to rocket warning sirens compared to participants without a psychiatric diagnosis (Gelkopf et al., 2017; Lapid Pickman et al., 2021). Regarding service use and help seeking, one large study observed no change and even a reduction in psychiatric outpatient visits and hospitalizations during the 2000–2002 Intifada in Jerusalem (Levav, 2006).…”
Section: Introductionmentioning
confidence: 66%
“…The first assessment wave was conducted in July–August during the 2014 Israel–Gaza war (see for example Gelkopf et al., 2019; Greene et al., 2020; Lapid Pickman et al., 2021). All participants were present in Israel and exposed to the war, when more than 4500 rockets and mortar shells were fired from Gaza on Israeli communities, and Israel conducted air and ground operations in Gaza.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted an a priori power analysis using the EMAtools R (Kleiman) package [75] for power curves for multilevel studies. The power analysis was based on two 3-week assessment bursts with 1 questionnaire per day and an estimated intraclass correlation coefficient of 0.36 based on a previous study on daily-level emotions, cognitions, and PTSD [76]. Analysis showed that 70 participants and up to 25% missing data would be sufficient to detect a medium effect size (d=0.5) with 80% power.…”
Section: Power Analysismentioning
confidence: 99%
“…Варто також зазначити, що непохитний спокій не обов'язково є реак цією на потрясіння здорової людини. Є спостереження, що більш мляво та байдуже на сповіщення повітряної три воги реагують якраз пацієнти з тривогою та депресією, а не здорові люди [5].…”
Section: вступunclassified